1979
DOI: 10.1111/j.1399-3054.1979.tb03197.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Salinity on Growth, Cation Content, Na+‐Uptake and Translocation in Salt‐Sensitive and Salt‐Tolerant Plantago Species

Abstract: Growth of salt‐sensitive Plantago media L. and salt‐tolerant P. coronopus L. and P. maritima L. was followed under saline conditions. Growth was reduced according to the ecological features of these species: P. media was sensitive to 25 mM NaCl, while P, coronopus and P. maritima could grow in 150 mM and 300 mM NaCl, respectively. The three Plantago species accumulated Na+ in the shoot and maintained a relatively low Na+ level in the root. K+. Mg2+ and Ca2+ levels of both shoots and roots decreased with increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
43
3
2

Year Published

1982
1982
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(55 citation statements)
references
References 13 publications
7
43
3
2
Order By: Relevance
“…4) decreased in salt treated plants to about 52% in spinach and 20% in pea relative to control leaves after 17 d. Ion uptake and/or transport competition under salinity has often been described (e.g. 5,16,22,25). Obviously, pea has a less well developed selectivity for the ion pair K+/Na+, and also for NO3-/C1L (Table II).…”
Section: Apoplastic Solute Concentrationsmentioning
confidence: 98%
“…4) decreased in salt treated plants to about 52% in spinach and 20% in pea relative to control leaves after 17 d. Ion uptake and/or transport competition under salinity has often been described (e.g. 5,16,22,25). Obviously, pea has a less well developed selectivity for the ion pair K+/Na+, and also for NO3-/C1L (Table II).…”
Section: Apoplastic Solute Concentrationsmentioning
confidence: 98%
“…At this time (time 0), 4 h after sunrise, 1-to 2-cm samples were taken from the terminal ends of the succulent stems. NaCl was then added to the culture solution to bring it to 100 mm NaCl, and samples were again taken at 2,4,6,8,12,16,20,24, 48, and 72 h after the addition of salt. Sampling was terminated at 72 h, because previous experiments indicated that 96% of the osmotic adjustment had occurred by this time, complete adjustment required 195 h. The samples were all taken from the terminal ends of the stems to insure similar ages and stages ofdevelopment ofthe tissues.…”
Section: Methodsmentioning
confidence: 99%
“…1b), offering an alternative, or additional, explanation of enhanced K + release under Na + exposure (Britto et al 2010;Coskun et al 2013). Combined, the above effects of impaired K + influx and enhanced efflux are expected to result in blockage of K + translocation to the shoot (Erdei and Kuiper 1979;Botella et al 1997;Kronzucker et al 2006;Munns and Tester 2008), with obvious consequences for downstream events such as photosynthesis and stomatal function.…”
Section: Sodium Toxicitymentioning
confidence: 99%